2010
DOI: 10.1111/j.1365-3148.2009.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood donor deferral causes in the Trinidad and Tobago National Blood Transfusion Service

Abstract: The majority of blood donations in Trinidad and Tobago are made as replacement by family members or friends. National Blood Transfusion Policy was drafted in 2007 to promote voluntary, repeated donation. The objective of this study is to assess the current rate and reasons for donor deferral, and the aim is to guide the proposed donor education and recruitment programme. A retrospective study of pre-donation deferral of prospective blood donors at the National Blood Transfusion Centre, Port of Spain, Trinidad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 12 publications
9
42
3
Order By: Relevance
“…In Nigeria, Olaiya et al (2004) found that only 7% of donations were voluntary, and that replacement donation-often for the donor's wife-was the norm. In Trinidad and Tobago, Charles et al (2010) observed that a great majority of blood donors are replacement donors (93, 7%) which also coincide with Parmasad (2012) and Sampath et al's (2007) results regarding the high percentage of family donation in the same country. These last authors point out that low participation in blood drives can also be attributed to the population's lack of information, an argument put forth by Polonsky et al (2011b) for African migrants in Australia.…”
Section: Blood Donation Among Ethnic Minoritiessupporting
confidence: 57%
“…In Nigeria, Olaiya et al (2004) found that only 7% of donations were voluntary, and that replacement donation-often for the donor's wife-was the norm. In Trinidad and Tobago, Charles et al (2010) observed that a great majority of blood donors are replacement donors (93, 7%) which also coincide with Parmasad (2012) and Sampath et al's (2007) results regarding the high percentage of family donation in the same country. These last authors point out that low participation in blood drives can also be attributed to the population's lack of information, an argument put forth by Polonsky et al (2011b) for African migrants in Australia.…”
Section: Blood Donation Among Ethnic Minoritiessupporting
confidence: 57%
“…Several studies have reported a similar deferral rate (5.20%) by Unnikrishnan et al [3], (6%) by Sundar et al [4], and (5.6%) by Rabeya et al [5]. Some studies have even had a higher deferral rate of (16.4%) Chaudhary et al [6], (35.6%) Charles et al [7]. Even though deferral rate were found to be similar, the major reasons for deferral varies reflecting disparity in socioeconomic status.…”
Section: Discussionmentioning
confidence: 77%
“…[8][9][10][11][12] However, studies by Rabeya et al & Kwa et al have cited low incidence (5.6-7.1%) to very high incidence by studies done by Charles et al, Di Lorenzo Oliveira et al and Madan et al (20-35. 6%). [13][14][15][16][17] The deferral incidence in their donor populations, which probably reflects the regional diversityand marked variation in whole blood donor eligibility criteria internationally. [18][19] The share of female donor was very small in the present study (6.39%) which was might be due to fear, lack of awareness and motivation among females.…”
Section: Resultsmentioning
confidence: 99%